Does risk culture matter for sustaining the business? evidence from Malaysian environmentally sensitive listed companies - Abdul Aziz, Nazliatul Aniza; Abdul Manab, Norlida (Conscientia Beam, 2020)
The aim of this paper is to examine how organisational risk culture and good risk management practices contribute to the sustainable business. Sustaining business requires a strong foundational of risk culture to address all types of risks. Having a sound risk culture is vital as it influences the way organisations respond to risks and hazards. A poor risk culture and weak risk management practices have triggered many business collapsed and lost with huge amounts. Drawing on the post-modern portfolio theory and stakeholder theory, the model in this study is empirically validated by means of the partial least squares approach to structural equation modelling (PLS-SEM) based on survey data from environmentally sensitive companies in Malaysia. Based on the analysis, the study revealed that risk culture moderates the relationship between the role of leadership and risk resilience of sustainability risk management (SRM) implementation and company survival. This result extend previous research by not only highlighting the importance of risk culture in driving effective SRM practices but also indicating the significance of risk resilience and leadership in sustaining the business.